DFT study of β-D-glucose adsorption on single-walled carbon nanotubes decorated with platinum: A bonding analysis - González Fá, Alejandro Javier (2017)
Adsorption of β-d-glucose onto Pt decorated carbon nanotubes (CNTs) was studied using density functional theory (DFT) methods including van der Waals (vdW) forces. Several adsorption geometries were analyzed evaluating the aptitude of different atoms fromβ-d-glucose molecule to be bonded with a Pt atom previously supported. The influence of vdW interactions in structure stabilization was also studied using overlap population (OP) and bonding order (BO) analysis. The results show strong short-range bonds between the O atoms from β-d-glucose and Pt decoration. The long-range interactions, mainly from O and H atoms from the adsorbate, demonstrate a significant contribution for stabilization of some geometric configurations. In effect, adsorption geometries where glucose interacts though the O atom of the ring or OH groups are favored by vdW forces, becoming the most stable systems. On the other hand, the geometry with the strongest OPt bond but a very small contribution from vdW interactions results less stable. DOS analysis shows the stabilization of β-d-glucose after adsorption and a strong chemical interaction with Pt/CNT.